Housing cycles in the UK: a historical and empirical investigation - Arayici, Yusuf; Pitros, Charalambos (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - The study looks at the characteristics of upswings and downswings for UK housing cycles. Specifically, the purpose of this paper is to empirically analyse cycles in house prices and housing affordability on the characteristics of persistence, magnitude and severity. Design/methodology/approach - The paper draws upon the triangular methodology of cycles and utilises housing data from the last three decades. Findings - From an empirical perspective, the study obtained four main results. First, the graphical trajectory of cycles in house price and housing affordability is highly synchronized. Second, upturns in both cycles tend to be longer than downturns on average. Third, the recent upturn in house prices and housing affordability is characterised by larger duration, magnitude and severity than the earlier case. Fourth, the latest downturn in both cycles is highly synchronised in terms of time occurrence, persistence, magnitude and severity; in addition, in both cases, the latest downturn is considerably smaller than the previous one. The study additionally indicates that on average the length of a complete house price and housing affordability cycle is 19 years on a peak-to-peak basis. Research limitations/implications - This paper is essentially exploratory and raises a number of questions for further investigation. Future research should, first, arrive at a more nuanced definition of affordability and, second, examine causality. The fact that two phenomena appear to have some significant synchronicity is not an indication that they are interdependent, although logic would suggest they might be. Originality/value - This is among the few papers that analyses cycles in UK house prices. It is the first study that draws attention to the housing affordability cycle and the first to compare cycles in house prices with cycles in housing affordability.
Keywords: Housing cycles; Housing affordability cycles; Property cycles; Real house prices